Control of an equation by maximum principle - Yıldırım, Kenan; Orhan Kutlu (Mustafa BAYRAM, 2016)
In this paper, some results, which are related to well posedness, controllability and optimal control of a beam equation, are presented. In order to obtain the optimal control function, maximum principle is employed. Performance index function is defined as quadratic functional of displacement and velocity and also includes a penalty in terms of control function. The solution of the control problem is formulated by using Galerkin expansion. Obtained results are given in the table and graphical forms.